Influence of cycle repetition on stack voltage degradation during fuel cell stress tests. Issue 3 (8th May 2022) - Yeetsorn, R.; Petrone, R.; Hissel, D.; Harel, F.; Breaz, E.; Gao, F.; Pera, M.C.
Abstract: A voltage decrease in the long‐term operation of hydrogen fuel cell (FC) electric cars under steady settings under constant load and dynamic operating conditions is a performance constraint of concern. Although accelerated stress test (AST) procedures have been sought to diagnose degradation, the AST results of FC stacks have not been reported extensively. The purpose of this article is to discuss the generation of AST of FC stacks based on real load profiles and the consequences of load changes and start‐stop circumstances, which are mostly generated by common driven cycles in urban regions with high driving speeds and traffic jams. The highlight of this study is to analyze the effects of cycle repetition on the aging FC stack, especially the voltage degradation factor, degradation kinetics, and energy consumption. The relation between actual system temperatures in side cells assembled in the FC stacks and material degradation was also analyzed. The results presented high heat accumulation, related to chemical degradation, that occurred during load cycling and may result in membrane thinning and pinholes in the membrane. Temperature cycling corresponded to mechanical degradation generated during the start‐stop cycling test, which may lead to membrane degradations—cracking, tearing, and pinholes.